(untitled) (Research, Society and Development, 2021)
Gastric artery embolization (GAE) is one of the minimally invasive therapies that have been studied as an alternative to bariatric surgery, in order to mitigate possible surgical complications. GAE has been performed for more than 40 years for the treatment of gastrointestinal hemorrhages, but more recently researchers have been studying the hypothesis that the procedure can be performed for anorexigenic purposes, associating the reduction in the production of the ghrelin hormone with the weight loss achieved. This systematic review aims to summarize the results obtained in the last 5 years, evaluating the efficacy and safety of GAE for anorexigenic purposes and its relation to the hormone ghrelin. Methodology: A cross-search was performed with the headings "gastric artery embolization" and "obesity", retrieved from DeCS / MeSH, in the Pubmed, MEDLINE and Cochrane Library databases. Results: This study revealed 87 obese patients undergoing embolization of the left gastric artery, with an average weight loss of 9.32% (T = 6.9 months) and an average reduction in serum ghrelin levels of 15.05% (T = 6 months). Discussion: So far, the results suggest that GAE may be a safe, but not effective, technique for the treatment of obesity. Final remarks: Considering that bariatric surgery provides sustained weight loss between 45-80% in up to 2 years, tests with higher N are needed to assess sustained weight loss proportionally to the drop in ghrelin levels, because the association between these variables is not proven statistically. In addition, longer-term research is needed to analyze potential long-term complications.